2019
DOI: 10.2478/enr-2019-0005
|View full text |Cite
|
Sign up to set email alerts
|

Expression of genes encoding IGF1, IGF2, and IGFBPs in blood of obese adolescents with insulin resistance

Abstract: Objective. The development of obesity and its metabolic complications is associated with dys-regulation of various intrinsic mechanisms, which control basic metabolic processes via changes in the expression of numerous regulatory genes. The main goal of this work was to study the association between the expression of insulin-like growth factors (IGF1 and IGF2) and IGF-binding proteins and insulin resistance in obese adolescents for evaluation of possible contribution of these genes in development of insulin re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 63 publications
(96 reference statements)
1
14
0
1
Order By: Relevance
“…Furthermore, hypoxia stimulates human preproendothelin-1 promoter activity in transgenic mice and in microvascular endothelial cells through interaction of transcription factor HIF with specific hypoxia responsible element in EDN1 promoter (Aversa et al 1997;Minchenko and Caro 2000). However, hypoxic regulation of the EDN1 gene expression is associated with protein kinases and functional activity of other transcriptional factors as well as with signaling pathways of endoplasmic reticulum stress (Minchenko and Caro 2000;Stow et al 2011;Minchenko et al 2015bMinchenko et al , 2017Tsymbal et al 2017;Zhang et al 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, hypoxia stimulates human preproendothelin-1 promoter activity in transgenic mice and in microvascular endothelial cells through interaction of transcription factor HIF with specific hypoxia responsible element in EDN1 promoter (Aversa et al 1997;Minchenko and Caro 2000). However, hypoxic regulation of the EDN1 gene expression is associated with protein kinases and functional activity of other transcriptional factors as well as with signaling pathways of endoplasmic reticulum stress (Minchenko and Caro 2000;Stow et al 2011;Minchenko et al 2015bMinchenko et al , 2017Tsymbal et al 2017;Zhang et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of hypoxia on the expression levels of endothelin-1 and its receptors (EDNRA and EDNRB) mRNAs as well as ECE1 and ACTB mRNAs were measured in control U87 glioma cells and cells with a deficiency of ERN1, introduced by dnERN1 and dnrERN1, by quantitative polymerase chain reaction using SYBRGreen Mix (ABgene, Thermo Fisher Scientific, Epsom, Surrey, UK) and qPCR "Rotor-Gene RG-3000" (Corbett Research, Germany) and "QuantStudio 5 Real-Time PCR System" (Applied Biosystems, USA). Thermo Scien tific Verso cDNA Synthesis Kit (Germany) was used for reverse transcription as described previously (Minchenko et al 2019). Polymerase chain reaction was performed in triplicate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of glucose deprivation on the expression levels of glucocorticoid receptor (NR3C1) and related proteins (NR3C2, ARHGAP35, AHR, NRIP1, NNT, SGK1, and SGK3 mRNAs as well as ACTB mRNA were measured in control U87 glioma cells and cells with a deficiency of ERN1 by quantitative polymerase chain reaction using SYBRGreen Mix (ABgene, Thermo Fisher Scientific, Epsom, Surrey, UK) and qPCR "RotorGene RG-3000" (Corbett Research, Germany) and "QuantStudio 5 Real-Time PCR System" (Applied Biosystems, USA). QuaniTect Reverse Transcription Kit (QIAGEN, Hilden, Germany) and Thermo Scientific Verso cDNA Synthesis Kit was used for reverse transcription as described previously (Minchenko et al 2015(Minchenko et al , 2019. Polymerase chain reaction was performed in triplicate.…”
Section: Reverse Transcription and Quantitative Pcr Analysismentioning
confidence: 99%
“…Regarding the associations between Let-7e and PPARG and between miR-144 and IGFBP2 , no previous studies were found showing such links. However, both genes are known to participate in the regulation of glucose and lipid metabolism [ 50 53 ] and our results suggest they can be targets of these miRNAs.…”
Section: Discussionmentioning
confidence: 76%